Morphine antidependence of Erythroxylum cuneatum (Miq.) kKurz in neurotransmission processes in vitro - Suliman, Noor Azuin; Mohd Moklas, Mohamad Aris; Mat Taib, Che Norma; Adenan, Mohd Ilham; Baharuldin, Mohamad Taufik Hidayat; Basir, Rusliza; Amom, Zulkhairi (Hindawi Publishing Corporation, 2016)
Opiate abuse has been studied to cause adaptive changes observed in the presynaptic release and the mediated-synaptic plasticity proteins. The involvement of neuronal SNARE proteins reveals the role of the neurotransmitter release in expressing the opioid actions. The present study was designed to determine the effect of the alkaloid extract of Erythroxylum cuneatum (E. cuneatum) against chronic morphine and the influences of E. cuneatum on neurotransmission processes observed in vitro. The human neuroblastoma cell line, SK-N-SH, was treated with the morphine, methadone, or E. cuneatum. The cell lysates were collected and tested for α-synuclein, calmodulin, vesicle-associated membrane protein 2 (VAMP 2), and synaptotagmin 1. The extract of E. cuneatum was observed to upregulate the decreased expression of dependence proteins, namely, α-synuclein and calmodulin. The effects were comparable to methadone and control. The expressions of VAMP 2 and synaptotagmin 1 were normalised by the plant and methadone. The extract of E. cuneatum was postulated to treat dependence symptoms after chronic morphine and improve the soluble N-ethylmaleimide-sensitive factor activating protein receptor (SNARE) protein involved in synaptic vesicle after.